Long-term experience with setup and implementation of an IHE-based image management and distribution system in intersectoral clinical routine - Schwind, Florian; Münch, H.; Schröter, A.; Brandner, R.; Kutscha, Ulrike; Brandner, Antje; Heinze, Oliver; Bergh, Björn; Engelmann, U. (International journal of computer assisted radiology and surgery, 2018)
PurposeSharing of medical data is crucial for the proper treatment of patients as it could reduce the risk of duplicated medical tests and speed up the care process if all documents are readily available. Despite great technical progress, sharing patient data while maintaining full control over the process in an intersectoral (in Germany, this describes the different actors in the healthcare system consisting of clinic, ambulatory care, etc.) setting remains a particular challenge. This paper focuses on the successful implementation of a privacy compliant, standards-based image-management component of a personal electronic health record.MethodsOver a 5-year period, a sharing system based on readily available IHE profiles constructed around XDS has been built. It was necessary to create interfaces for the existing hospital sub-systems to become part of the network. Specifically, the imaging workflow had to be adapted to allow for fast and easy access to DICOM images utilizing a flexible web-based image viewer. In addition to the standard XDS workflow, an Imaging Cache was established which combines the Imaging Document Source and Consumer to guarantee fast and streaming-based access to all images in the network observing the high security standards of the hospital network.ResultsThe authors of this paper have proven that it is possible to build a fast and reliable sharing system based on IHE profiles using most of the transactions of XDS-I with some adaptions to the clinical workflow. Primary hospital systems were enabled by building adapters to overcome lack of IHE compatibility. The established system embraces the existing security mechanisms in hospital networks while connecting patients and referring physicians from outside in a secure and convenient manner.ConclusionsA state-of-the-art sharing system that is used in a productive clinical environment has been established and is ready to grow with more partners. The system is the basis for an elaborated interdisciplinary collaboration where data, and in particular images, can now be shared between medical professionals.
Gesehen am 04.09.2019